Attraction and Repulsion in Louis MacNiece's poetry - Hamdan, Majid (Al-Adab Journal, 2025)
There are incidents in some people's lives which have a great impact on their behavior, work and even their belonging to an extent they undermine the voice to become a tide in vanishing and surfacing at different times. This paper aims to demonstrate the ups and downs of the Irish poet Louis MacNiece in looking at his native country, Ireland, in general, and the west in particular in comparison to other places and the criterion with which he could stand on that slippery ground to avoid slander and non- belonging. His deep and powerful emotion toward his country makes him a tourist who views the vistas from afar and comments as a true outsider exploring the condition of the world mixing between his inner thoughts instigated by social, religious, or cultural motivations with what he must be as a citizen.